The Role of Schools in Shaping Student Character at SMAIT Nur Hidayah Sukoharjo - Alief Ilhan Rahmatullah; Mohammad Zakki Azani (SAINTIS Publishing, 2025)
Character education is an essential aspect of the national education system but often takes a lower priority compared to academic achievement. In Islam, morality aligns with the goals of education, and its formation can be achieved through role modeling and habituation. This study examines school strategies in shaping students' character and the challenges faced, with the hope of providing insights and solutions for its implementation. This research is qualitative, providing a comprehensive overview of the school's role in character formation. Data was collected through interviews. SMAIT Nur Hidayah Sukoharjo implements character education by integrating Islamic values into the curriculum, religious activities, and a school culture that supports the development of noble character. The school’s vision and mission align with the goals of character education, aiming to produce a generation that is morally upright, independent, and responsible. Moreover, various flagship programs such as halaqah tarbawiyah, mentoring, worship habituation, and social activities serve as effective means for internalizing character values. It can be concluded that the school has a strong commitment to building students' character through systematic programs and methods. Character education is not only implemented in classroom learning activities but also in extracurricular activities, daily habits, and social interactions between teachers, students, and the school environment.